Revealing the Structure of Financial Performance on Stock Prices - Faizul Mubarok (LPPM Universitas Terbuka, 2022)
Purpose – Businesses are required to be able to present evidence of successful financial performance. The purpose of this research is to examine the relationship between specific financial ratios and the stock market performance of corporations in the infrastructure, utility, and transportation sectors. Methodology – This study employs panel data regression with quarterly reports from 6 companies from 2015 to 2020. Variables such as stock prices, total asset turnover, the debt to equity ratio, the return on assets, the price to book value, the size of the firm, and the current ratio are analyzed. Findings – Total asset turnover was found to have little effect on stock prices compared to other metrics such as the current ratio, firm size, price to book value, return on assets, and debt to equity ratio. It is imperative that businesses pay attention to the ratio indicators that persistently impact stock prices. Large swings in financial ratios are associated with an increased risk as well as a decline in public trust. Originality – This study extends the scope of previous research by extending the fundamental factors that are not only centered on liquidity, solvency, and profitability, but also with new variations, specifically the ratio of total asset turnover and price to book value. Additionally, this study adds new information to the fundamental factors that are not only centered on liquidity, solvency, and profitability.